DESIGNED TO BUILD WEB-BASED LIBRARY INFORMATION SYSTEM AT SMK SENOPATI - Arda Fikri Saudi; Tri Sagirani; Norma Ningsih (Jurnal Sistem Informasi Universitas Dinamika, 2020)
Senopati Vocational School is a school that located in Sidoarjo. The business process in the Senopati Vocational School library currently implementing a manually service process that all the data collection and recording are still written in the book, so when searching for the data that is needed there must open the book page by page. This causes the slow search for book data. The registration process for members is also increasingly difficult because of the increasing number of students. Making reports that still done by recording all transactions into a special recipe book to record all the results of service activities in the library every day and every month. The solution that applied to resolve these problems is by creating a Web-based Library Information System Design that can helpful in the book registration process, library member registration, book lending processes, book development process fines for delays in returning books and making reports processes that be required by the library. Based on the results of the trials on the Senopati Vocational Library system, the results of this library information system were able to facilitate the book registration process, member registration, loan process, return process, and making reports